DÖRT TEKERLİ HİBRİT KAPALI KASA BİSİKLET TASARIMI VE ÜRETİMİ - ARSLAN, MEHMET (Fırat Üniveristesi, 2022)
Bu çalışmada şehir içi ulaşımında kullanılacak hibrit bisiklet modellemesi ve üretimi yapılarak kent içinde kullanılan fosil yakıtlı araçlara bir alternatif olarak sunulması amaçlanmaktadır. Hibrit bisiklet ile elektrik desteği sayesinde farklı yaş ve cinsiyet guruplarına konforlu bir kullanım ve kapalı kasa sistemi ile kötü hava şartlarından etkilenmeden güvenli bir sürüş sunmak hedeflenmiştir. Projede, katma değeri yüksek hem ulusal hem uluslararası alanda kabul görmüş marka değeri olan bir hibrit bisiklet modeli üretimi gerçekleştirilmiştir. Şehir içi ulaşımda kullanılmak üzere elektrik motoru, Li-on batarya ve güneş enerji panelleri kullanılarak pedal destekli kapalı kasa hibrit bisiklet modeli geliştirilmiştir. Bisiklet modeline entegre edilen arduino tabanlı sistem ve bluetooth ile haberleşen mobil uygulama sayesinde otonom araçların

The use of electric bicycles is presented as a solution to the noise and air pollution due to the rise in vehicle density and increasing population as well as the conditions that negatively affect human health and urban life and its use in developed countries has been becoming more widespread. For this reason, electric bicycles are often seen as candidate vehicles that have become a part of daily life. In this study, it is aimed to design and produce hybrid bicycles to be used in urban transportation and to present them as an alternative to fossil fuel vehicles used in the city. With this hybrid bike, it is sought to offer a comfortable use to different age and gender groups thanks to the electric support, and a safe ride with the closed box system without being affected by bad weather conditions. In the project, a hybrid bicycle model with high added value and recognized brand value both nationally and internationally was produced. A pedal-assisted closed body hybrid bicycle model was developed to be used in urban transportation by using electric motor, Li-on battery and solar energy panels. The study has contributed to the development of autonomous vehicles thanks to the arduino-based system integrated into the bicycle model and the mobile application communicating with bluetooth. Therefore, with the help of developing technology, this study expands the research on developing new transportation vehicles that are environmentally friendly use renewable energy sources, with the least cost in order to meet the needs of people in the transportation sector, as in all other sectors.
Four whell hybrid closed frame bicycle design and production
Keywords: Makine Mühendisliği; Ulaşım